The Influence of Islamic Content on Instagram Through Product Attractiveness Towards Corporate Image - Ruvira Arindita; Kussusanti Kussusanti; Nursalsa Arifah (Universitas Prof. Dr. Moestopo (Beragama), 2023)
Moslem fashion trend followed by the advancement of information technology in the past years have enabled hijab online business to flourish. Persuasive communication with followers via Instagram is crucial. Moreover, competition among hijab online shops encouraged brands to build corporate image so that they look good for the public. The article aimed to know the influence of persuasive communication on the Islamic content of Hijab Online Shop’s Instagram account influence corporate image with moderation of product attractiveness. This study uses quantitative method with positivism paradigm. The theory used is functional theory, product attractiveness and corporate image. The population of this research is followers of the three hijab online shops that are the most active in terms of posting the Islamic content: @vanillahijab, @alezalabel and @hijup. The sampling method was conducted purposively, with the total sample 100 people. The result indicates that there is influence of persuasive communication in Islamic content of hijab online shop’s Instagram account towards the corporate image and the influence increases as product attractiveness increases. Knowledge as part of persuasive communication is the most influential aspect among other persuasive communication elements. Other than that, product attractiveness remained as supportive factor in building corporate image.